Peranan Sistem Informasi Akuntansi Piutang Terhadap Pengendalian Piutang (Studi Kasus Pada Pt. Arwinda Perwira Utama) - J.K, Andryan Elfani; Nurjanah, Yayuk; Munawar, Aang (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
Knowledge and technology today is rapidly developing, resulting in a very tight competition in the business world. Firms that can stand should be able to survive by various means. There are several ways to maintain the company's business continuity, one of which is by paying close attention to the system run in the company. One of the systems that must be considered is the sales system and the collection process of receivables. This is because sales are activities that will generate income or profit into the company for further business continuity. In the receivables collection process, management will have to address the issue in the billing process because it will determine if the returns. The purpose of this study is to identify the accounting information system of receivables, to identify the accounting information system on billing process of receivables, and accounting information system on collection process of receivables at PT. Arwinda Perwira Utama. The author conducted research at PT Arwinda Perwira Utama - Bogor. The results of research show that the company has run a fairly proper sales accounting information system in the collection process of receivables, because it has an appropriate internal control elements. However, there are still some activities and functions that need to be address immediately, such as sales function, credit authorization function, and collection function. In addition, there are documents that still do not use printed serial number. The relationship between the sales process and the billing process has been quite well-synchronized, and it can be seen from the turnover of receivables.